Operationalising positive tipping points towards global sustainability. (10th January 2022) - Lenton, Timothy M.; Benson, Scarlett; Smith, Talia; Ewer, Theodora; Lanel, Victor; Petykowski, Elizabeth; Powell, Thomas W. R.; Abrams, Jesse F.; Blomsma, Fenna; Sharpe, Simon
Abstract : Non-technical summary: Transforming towards global sustainability requires a dramatic acceleration of social change. Hence, there is growing interest in finding 'positive tipping points' at which small interventions can trigger self-reinforcing feedbacks that accelerate systemic change. Examples have recently been seen in power generation and personal transport, but how can we identify positive tipping points that have yet to occur? We synthesise theory and examples to provide initial guidelines for creating enabling conditions, sensing when a system can be positively tipped, who can trigger it, and how they can trigger it. All of us can play a part in triggering positive tipping points. Technical summary: Recent work on positive tipping points towards sustainability has focused on social-technological systems and the agency of policymakers to tip change, whilst earlier work identified social-ecological positive feedbacks triggered by diverse actors. We bring these together to consider positive tipping points across social-technological-ecological systems and the potential for multiple actors and interventions to trigger them. Established theory and examples provide several generic mechanisms for triggering tipping points. From these we identify specific enabling conditions, reinforcing feedbacks, actors and interventions that can contribute to triggering positive tipping points in the adoption of sustainable behaviours and technologies. Actions that can create enabling conditions for positive tipping include targeting smaller populations, altering social network structure, providing relevant information, reducing price, improving performance, desirability and accessibility, and coordinating complementary technologies. Actions that can trigger positive tipping include social, technological and ecological innovations, policy interventions, public investment, private investment, broadcasting public information, and behavioural nudges. Positive tipping points can help counter widespread feelings of disempowerment in the face of global challenges and help unlock 'paralysis by complexity'. A key research agenda is to consider how different agents and interventions can most effectively work together to create system-wide positive tipping points whilst ensuring a just transformation. Social media summary: We identify key actors and actions that can enable and trigger positive tipping points towards global sustainability.